Author Correction: A multi-cohort study of the immune factors associated with M. tuberculosis infection outcomes. (6th December 2018) - Roy Chowdhury, Roshni; Vallania, Francesco; Yang, Qianting; Lopez Angel, Cesar; Darboe, Fatoumatta; Penn-Nicholson, Adam; Rozot, Virginie; Nemes, Elisa; Malherbe, Stephanus; Ronacher, Katharina; Walzl, Gerhard; Hanekom, Willem; et al.
The spelling of author Qianting Yang was corrected; the affiliation of author Stephanus T. Malherbe was corrected; and graphs in Fig. 4b and c were corrected owing to reanalysis of the data into the correct timed intervals.